2019
DOI: 10.1057/s41599-018-0211-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prestige on collective performance and information flow in a strictly hierarchical institution

Abstract: Institutions such as the military aim to respond efficiently to complex logistical challenges using a strictly hierarchical structure, where leaders are assigned a rank by senior colleagues and team members are trained to obey leader commands. Anthropologists have observed that leadership status outside of these top-down hierarchical institutions is often affected by the attribution of prestige by non-leaders. Here we show that even in the strictly hierarchical institutional context of the Royal Navy, informal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Likewise, experimental and ethnographic studies suggest that leader fairness and charisma can positively affect cooperation [33]. There is evidence in strictly hierarchical institutions that team performance and information flow is correlated with the degree of informal prestige conferred upon leaders [34,35] although, contrary to common marketing strategy, there is also evidence that real-life cooperative behaviours are not highly influenced by celebrity endorsement [36,37]. Formal status or rank has received little attention, although one social dilemma experiment found participants labelled with stars (indicating a superior quiz performance) were copied more than those without stars [38].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, experimental and ethnographic studies suggest that leader fairness and charisma can positively affect cooperation [33]. There is evidence in strictly hierarchical institutions that team performance and information flow is correlated with the degree of informal prestige conferred upon leaders [34,35] although, contrary to common marketing strategy, there is also evidence that real-life cooperative behaviours are not highly influenced by celebrity endorsement [36,37]. Formal status or rank has received little attention, although one social dilemma experiment found participants labelled with stars (indicating a superior quiz performance) were copied more than those without stars [38].…”
Section: Introductionmentioning
confidence: 99%
“…And a small-scale survey in Kyrgyzstan explored what qualities people wished to see in their political leaders and found that, in order of frequency of mention, these were patriotism, a good education (graduate level), honesty, political professionalism, charisma, intelligence, responsibility, strength of character, service to the people and bravery (Murzaeva and Akçali, 2013). Anthropologists have observed that leadership status is often affected by the attribution of prestige to those in leadership positions by non-leaders; even in a strictly hierarchical cultural context, informal prestige networks play a functional role in the efficacy of leadership and group dynamics (Offord et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Leader prestige has also been found to improve employee's trust in leader, organizational commitment, and job satisfaction (Case & Maner, 2014;He et al, 2015). Furthermore, following an examination of leader prestige in a hierarchical institution (i.e., the military), Offord et al (2019) found that leaders high in prestige, regardless of rank, were able to disseminate information more efficiently compared to leaders low in prestige, suggesting that colleagues value and accept information coming from a prestigious leader, and behave accordingly. While these findings may not directly support an association between leader prestige and CWB, taken together, they suggest that supervisors high in prestige may positively influence followers through imitation and social learning (Bandura, 1977), which may relate to decreases in negative employee behaviours such as CWB.…”
Section: Leader Dominance and Prestigementioning
confidence: 99%